ChemInform Abstract: The Study of Catalyst Free and Copper Catalyzed Reactions of Cyanochromenes and Sodium Azide. Issue 24 (23rd May 2013) - Gawande, Sachin D.; Raihan, Mustafa J.; Zanwar, Manoj R.; Kavala, Veerababurao; Janreddy, Donala; Kuo, Chun‐Wei; Chen, Mei‐Ling; Kuo, Ting‐Shen; Yao, Ching‐Fa
Abstract Two different roles of sodium azide under two different reaction conditions are described.